2018
DOI: 10.1177/1094428117753683
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Applicant Faking on Forced-Choice and Likert Scores

Abstract: We introduce a novel, regression-based moderation framework to model faking effects that incorporates evaluation of faking tendency as a moderator. We also consider how perceived trait desirability may be factored into the framework and provide programming code for applied researchers to utilize the method in their research. Using this framework, we revisit a well-known response format (i.e., forced-choice) to formally evaluate its ability to mitigate the effects of applicant faking as compared to the widely u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 95 publications
1
40
1
Order By: Relevance
“…SS measurement is, however, not without issues. Faking and rating scale errors, such as halo, acquiescent responding, extreme response style, and midpoint response style, lead to serious concerns (e.g., Donovan, Dwight, & Schneider, 2014; Landy & Farr, 1980; Pavlov, Maydeu-Olivares, & Fairchild, 2018). An alternative that was originally developed to overcome problems with SS measures was the forced-choice (FC) scale (Rundquist, 1946).…”
mentioning
confidence: 99%
“…SS measurement is, however, not without issues. Faking and rating scale errors, such as halo, acquiescent responding, extreme response style, and midpoint response style, lead to serious concerns (e.g., Donovan, Dwight, & Schneider, 2014; Landy & Farr, 1980; Pavlov, Maydeu-Olivares, & Fairchild, 2018). An alternative that was originally developed to overcome problems with SS measures was the forced-choice (FC) scale (Rundquist, 1946).…”
mentioning
confidence: 99%
“…However, in natural settings, applicants' tendency to fake can play an important role. Pavlov, Maydeu-Olivares, and Fairchild (2019) showed using a regression-based moderation analysis that faking was only reduced for the forced-choice format at high faking tendency levels, though they did not match the forced-choice items regarding desirability. This implies that future research conducted in natural settings should also take participants' propensity for faking into account.…”
Section: Limitations and Future Directionsmentioning
confidence: 97%
“…In addition to meta-analyses, which consider the fakeability of one response format (Likert vs. FC) in isolation, individual studies that have drawn a direct comparison can also be used to assess the relative susceptibility to faking. In fact, the vast majority of these studies found faking-induced score inflation to be smaller for FC scales (Christiansen et al, 2005;Huber, 2017;Jackson et al, 2000;Lee et al, 2019;Pavlov et al, 2019;Vasilopoulos et al, 2006); but, see Heggestad et al (2006) for contrary results.…”
Section: Overall Faking Effectsmentioning
confidence: 98%
“…It is particularly important for potential faking in personnel selection, since faking in this context would be closely linked to changes in applicants' rank order and, therefore, is directly relevant to selection decisions. While one study, showed that FC scores from an applicant condition explained more "true" trait variance than their Likert scale counterparts (Christiansen et al, 2005), other studies have failed to consistently show that discrete FC scales are superior (Guan, 2015;Heggestad et al, 2006;Pavlov et al, 2019). This might be a consequence of reliability issues associated with discrete FC measures (Guan, 2015;Pavlov et al, 2019) or for the study by Heggestad and colleagues (2006), an artifact of ipsative scoring methods.…”
Section: Overall Faking Effectsmentioning
confidence: 99%
See 1 more Smart Citation